1985
DOI: 10.1093/nar/13.10.3561
|View full text |Cite
|
Sign up to set email alerts
|

The effect of salt extraction on the structure of transcriptionally active genes; evidence for a DNAseI-sensitive structure which could be dependent on chromatin structure at levels higher than the 30 nm fibre

Abstract: The procedure developed by Lawson and Cole (Biochemistry, 1979, 18 2161-2166) for removing lysine-rich histones from nuclei at low pH also quantitatively extracts proteins HMG14 and 17. The effect of this low pH extraction on the DNAseI-sensitive structures of active genes in avian red blood cells has been investigated. No major perturbation of a developmentally regulated DNAseI hypersensitive site in the beta-globin domain and at the 5' end of the alpha D gene was seen. The overall DNAseI-sensitive conformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…A long-standing assumption has been that nuclease sensitivity is the result of a more open or decondensed chromatin structure, but to date no direct molecular evidence supports this. Studies using limited trypsin digestion (38) or extraction under high salt conditions (21) suggested that chromatin higher-order structure, or at least higher-order structure dependent upon linker histones or high-mobility-group proteins, was not related to nuclease sensitivity. While our results show that histone acetylation and H3 K4 dimethylation may also be ruled out, other histone modifications that we have not tested might better correlate with the nuclease-sensitive structure; the list of known covalent histone modifications is already very long and continues to grow.…”
Section: Discussionmentioning
confidence: 99%
“…A long-standing assumption has been that nuclease sensitivity is the result of a more open or decondensed chromatin structure, but to date no direct molecular evidence supports this. Studies using limited trypsin digestion (38) or extraction under high salt conditions (21) suggested that chromatin higher-order structure, or at least higher-order structure dependent upon linker histones or high-mobility-group proteins, was not related to nuclease sensitivity. While our results show that histone acetylation and H3 K4 dimethylation may also be ruled out, other histone modifications that we have not tested might better correlate with the nuclease-sensitive structure; the list of known covalent histone modifications is already very long and continues to grow.…”
Section: Discussionmentioning
confidence: 99%
“…Generalized nuclease sensitivity is a property inherent in all actively expressed genes (Gazit and Cedar 1980), correlating closely with the presence of acetylated histones. Whether a cause or an effect, the presence of acetylated histones accompanies the appearance of open chromatin extending over 10s to 100s of kilobases and is documented in the chicken lysozyme, chicken ovalbumin, human apolipoprotein B, c-fos, and chicken ␤-globin loci (Lawson et al 1982;Goodwin et al 1985;Jantzen et al 1986;Feng and Villeponteau 1992;Hebbes et al 1994). In contrast, hypersensitivity refers to regions showing extreme sensitivity to the cleavage effects of the enzyme that are localized to short stretches of DNA ranging from 100 to 400 bp in length (Gross and Garrard 1988).…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…Neither over-expressing topoisomerase I nor pre-nicking DNA with MNase prior to DNase I digestion of nuclei reverses the split nucleosomal structures (data not shown), indicating that maintenance of the structures does not require torsional stress. Nevertheless, DNase I sensitivity and half-nucleosomal cutting patterns have proven difficult to preserve upon mononucleosome isolation (Lohr and Van Holde, 1979;Goodwin et al, 1985). The insoluble chromatin associated with active genes may be composed of a split nucleosome structure (see Xu et al, 1986).…”
Section: Short-term Versus Long-term Memory In Chromatinmentioning
confidence: 99%